(untitled) (ModaPalavra e-periódico, 2023)
This article aims to present a chronology of illustrated works with a historical bias on clothing, since the publication of Trachtenbuch (1560), by Matthäus Schwarz. A set of works considered canonical will be listed because they present important aspects of the process of use and circulation of costume images, divided into categories: clothing books, costume books, habits engraving books, great illustrated books, romantic/historicist books and modern books. This mapping and classification, carried out in a doctoral thesis through bibliographic review and documental research, resulted in 35 works surveyed and a clipping with 25 books will be presented in these pages, in addition to the highlight of the book Três Séculos de Modas (1923), by João Affonso, a pioneering work of the genre in Brazil. This production helped us to reflect on how the construction of an imaginary about clothing was present in publications that will give rise to the field of clothing history.